2018
DOI: 10.3233/com-170071
|View full text |Cite
|
Sign up to set email alerts
|

Partial orders and immunity in reverse mathematics

Abstract: Abstract. We identify computability-theoretic properties enabling us to separate various statements about partial orders in reverse mathematics. We obtain simpler proofs of existing separations, and deduce new compound ones. This work is part of a larger program of unification of the separation proofs of various Ramsey-type theorems in reverse mathematics in order to obtain a better understanding of the combinatorics of Ramsey's theorem and its consequences. We also answer a question of Murakami, Yamazaki and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…They also showed that none of these principles imply WKL 0 over RCA 0 . The fact that CAC is properly stronger than ADS was first proved by Lerman, Solomon, and Towsner [LST13], and then given a simpler proof by Patey [Pat16]. These results support the idea that RT 2 2 , in contrast to the big five, is not robust (Montalbán [Mon11] informally defined a theory to be robust "if it is equivalent to small perturbations of itself").…”
Section: Reverse Mathematicsmentioning
confidence: 70%
“…They also showed that none of these principles imply WKL 0 over RCA 0 . The fact that CAC is properly stronger than ADS was first proved by Lerman, Solomon, and Towsner [LST13], and then given a simpler proof by Patey [Pat16]. These results support the idea that RT 2 2 , in contrast to the big five, is not robust (Montalbán [Mon11] informally defined a theory to be robust "if it is equivalent to small perturbations of itself").…”
Section: Reverse Mathematicsmentioning
confidence: 70%
“…No arrows reverse. Proofs of these implications and separations may be found in [6,8,16,17,21,22,26,29,30].…”
Section: Reverse Mathematics Backgroundmentioning
confidence: 99%
“…Patey [Pat15] proved that EM admits avoidance of constant-bound traces for ω closed sets. On the other hand, Rice [Ric] constructed a computable instance of EM such that every solution computes a diagonally non-computable function, while Patey [Pat16a] constructed a ∆ 0 2 immune set A such that every diagonally non-computable function computes an infinite subset of A. This shows that EM does not admit preservation of 1 immunity.…”
Section: The Hierarchy Of Preservationsmentioning
confidence: 99%